Risk Factors for H9N2 Contamination in Live Bird Markets of the Greater Jakarta, Indonesia - Rahma Hani Aisah; Bambang Sumiarto; Hendra Wibawa; Widagdo Sri Nugroho; Aprizal Panus; Sodirun Sodirun (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2023)
Low Pathogenicity Avian Influenza virus subtype H9N2 causes decreased egg production and two of the four defined H9N2 poultry lineages (G1 and Y280) have been associated with human infections. The high positive test results for the H9N2 virus in the LBMs of the Greater Jakarta area in 2021 can be a source of transmission for the surrounding area. This study aims to determine the prevalence and risk factors that play a role in the H9N2 contamination in the LBMs to obtain a multivariate analysis model. A cross-sectional study was conducted on 87 vendors and 124 broiler chickens from 44 LBMs randomly selected in Tangerang City, North Jakarta, and Bekasi City. Samples were taken as equipment swabs at the stall of poultry carcass vendors, tracheal swabs, and cloacal swabs of broiler chicken. The test used was Real-Time Reverse Transcription Polymerase Chain Reaction. Data analysis was performed using univariate, bivariate, and multivariate analysis with logistic regression. The prevalence of H9N2 virus contamination at the LBM level in Greater Jakarta in 2022 was 77.27% (95% CI, α 7%), while the prevalence at the vendor level was 54.02% (95% CI, α 5%). The risk factors for H9N2 virus contamination with a significant p-value<0.05 include the positive results on equipment swab samples, positive results on both equipment and broiler swabs, and the use of carcass sink. The multivariate analysis model of H9N2 virus contamination at the vendor level was Logit P (H9N2=1 | x) = 0.29924 - 2.42176PPE + 1.58691carcass sink. The risk factor contributing to increase H9N2 contamination is using carcass sinks, while PPE is the one that reduces H9N2 contamination.